The Role of English in Preparing Students to Face Global Challenges - Haryadi, Rofiq Noorman; Aminuddin, Muhammad (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
Globalization has had a significant impact on various sectors of life, including education. English has become the dominant international language in cross-cultural communication and global business transactions. This research aims to investigate the role of English in preparing students to face global challenges. This study involves an in-depth analysis of how English language proficiency can help students overcome global challenges, including cross-cultural communication, access to global resources, and preparation for the global job market. Through a qualitative approach, data is collected through interviews and surveys of students who have been involved in educational programs with an international focus. The results of this research provide insight into the importance of mastering English in facing global challenges, as well as the challenges faced by students in developing their language skills. The conclusions of this research emphasize the need for better integration between English language learning and educational curricula to better prepare students to face global challenges.